Externalities, scarcity, and abundance - Frischmann, Brett M.; Ramello, Giovanni B. (Frontiers in Research Metrics and Analytics, 2023)
Do externalities work and matter differently in a world of scarcity versus a world of abundance? In this article, we critically examine the economic phenomena of externalities. First, we define the basic concept and explain why it is fundamental to economic analysis of social systems. As a conceptual tool, externalities enable one to identify and examine social interdependencies and to map their causes and consequences. Externalities provide evidence of social demand for governance institutions. This descriptive utility can and should inform normative analysis, the design of governance institutions, and comparative institutional analysis. Second, we briefly survey the intellectual history of externalities with the goal of tying together a few different strands of economic theory and providing a roadmap for a general theory of externalities. This discussion highlights a latent conflict between those who pursue and those who resist perfectibility (optimization) of social systems by internalizing externalities. Third, we compare externalities in worlds of scarcity and abundance. We focus on the scarcity and abundance of knowledge resources and the (technological) means for participating in the production, dissemination, and modification of such resources. In the real, necessarily imperfect world where abundance and scarcity vary across resources, people, and contexts, externalities persist, indicate social demand for governance, and inform comparative analysis and design of governance institutions. We raise a series of (mostly empirical) questions that should frame evaluation of different externalities in the digital networked world.